Quercetin prevents osteoarthritis progression possibly via regulation of local and systemic inflammatory cascades. Issue 4 (1st February 2023) - Wang, Haiyan; Yan, Yongyong; Pathak, Janak L.; Hong, Wei; Zeng, Jing; Qian, Dongyang; Hao, Binwei; Li, Haiqing; Gu, Jinlan; Jaspers, Richard T.; Wu, Gang; Shao, Ming; et al.
Abstract: Due to the lack of effective treatments, osteoarthritis (OA) remains a challenge for clinicians. Quercetin, a bioflavonoid, has shown potent anti‐inflammatory effects. However, its effect on preventing OA progression and the underlying mechanisms are still unclear. In this study, Sprague–Dawley male rats were divided into five groups: control group, OA group (monosodium iodoacetate intra‐articular injection), and three quercetin‐treated groups. Quercetin‐treated groups were treated with intragastric quercetin once a day for 28 days. Gross observation and histopathological analysis showed cartilage degradation and matrix loss in the OA group. High‐dose quercetin‐group joints showed failure in OA progression. High‐dose quercetin inhibited the OA‐induced expression of MMP‐3, MMP‐13, ADAMTS4, and ADAMTS5 and promoted the OA‐reduced expression of aggrecan and collagen II. Levels of most inflammatory cytokines and growth factors tested in synovial fluid and serum were upregulated in the OA group and these increases were reversed by high‐dose quercetin. Similarly, subchondral trabecular bone was degraded in the OA group and this effect was reversed in the high‐dose quercetin group. Our findings indicate that quercetin has a protective effect against OA development and progression possibly via maintaining the inflammatory cascade homeostasis. Therefore, quercetin could be a potential therapeutic agent to prevent OA progression in risk groups.